Effects of push-up exercise on shoulder stabilizer muscle activation according to the grip thickness of the push-up bar - Jung, Jaemin (J Phys Ther Sci, 2015)
[Purpose] This study investigated the effects of bar thickness on shoulder stabilizer muscle activation during push-up exercise. [Subjects] Twenty-six healthy male adults in their twenties. [Methods] The study had four experimental conditions (grip thicknesses of 0%, 50%, 75%, and 100% of the subjects’ hand size). Measurements were conducted from the start to the end of push-up for deltoid anterior fiber, deltoid posterior fiber, infraspinatus, serratus anterior, and pectoralis major muscle activation. [Results] The deltoid anterior fiber muscle activity was 4,852.6 ± 975.2 in the 0%, 5,787.3 ± 1,514.1 in the 50%, 5,635.3 ± 1,220.1 in the 75%, and 5,032.9 ± 841.0 in the 100% condition. The infraspinatus muscle activity was 1,877.2 ± 451.3 in the 0%, 2,310.9 ± 765.4 in the 50%, 2,353.6 ± 761.9 in the 75%, and 2,016.8 ± 347.7 in the 100% condition. The pectoralis major muscle activity was 1,675.8 ± 355.1 in the 0%, 2,365.5 ± 1,287.3 in the 50%, 2,125.3 ± 382.5 in the 75%, and 1,878.8 ± 419.7 in the 100% condition, showing significant differences respectively. [Conclusion] The use of push-up bars with different thicknesses customized to personal characteristics, rather than the conventional standard, could be more effective for training and rehabilitation.